COMPARATIVE ANALYSIS OF ADHERENCE TO CASTRATION AND MICROCHIPPING IN DOGS AND CATS IN THE MUNICIPALITY OF PAUDALHO, PERNAMBUCO, BRAZIL (REMUNOM, 2026)
This study is part of the extension project “More Safety in One Health”, conducted in Paudalho-PE, Brazil, aiming to analyze pet owners’ adherence to the castration and microchipping of dogs and cats, as well as the factors influencing participation. Castration and microchipping are complementary strategies for population control and responsible ownership promotion, contributing to the reduction of stray animals and the prevention of zoonoses. The study was carried out from July to September 2025, covering 284 animals — 141 dogs and 143 cats —, with 45 microchipped. Greater adherence to castration was observed compared to microchipping, with females showing higher participation rates. The low acceptance of microchipping was mainly related to lack of knowledge and misconceptions about the procedure. The results highlight the need for educational programs and awareness campaigns, emphasizing castration and microchipping as effective tools to strengthen One Health principles, benefiting animal, human, and environmental health.